The effectiveness of art therapy for anxiety in adults: A systematic review of randomised and non-randomised controlled trials - Abbing, Annemarie; Ponstein, Anne; van Hooren, Susan; de Sonneville, Leo; Swaab, Hanna; Baars, Erik (PLOS ONE, 2018)
Background Anxiety disorders are one of the most diagnosed mental health disorders. Common treatment consists of cognitive behavioral therapy and pharmacotherapy. In clinical practice, also art therapy is additionally provided to patients with anxiety (disorders), among others because treatment as usual is not sufficiently effective for a large group of patients. There is no clarity on the effectiveness of art therapy (AT) on the reduction of anxiety symptoms in adults and there is no overview of the intervention characteristics and working mechanisms. Methods A systematic review of (non-)randomised controlled trials on AT for anxiety in adults to evaluate the effects on anxiety symptom severity and to explore intervention characteristics, benefitting populations and working mechanisms. Thirteen databases and two journals were searched for the period 1997 –October 2017. The study was registered at PROSPERO (CRD42017080733) and performed according to the Cochrane recommendations. PRISMA Guidelines were used for reporting. Results Only three publications out of 776 hits from the search fulfilled the inclusion criteria: three RCTs with 162 patients in total. All studies have a high risk of bias. Study populations were: students with PTSD symptoms, students with exam anxiety and prisoners with prelease anxiety. Visual art techniques varied: trauma-related mandala design, collage making, free painting, clay work, still life drawing and house-tree-person drawing. There is some evidence of effectiveness of AT for pre-exam anxiety in undergraduate students. AT is possibly effective in reducing pre-release anxiety in prisoners. The AT characteristics varied and narrative synthesis led to hypothesized working mechanisms of AT: induce relaxation; gain access to unconscious traumatic memories, thereby creating possibilities to investigate cognitions; and improve emotion regulation. Conclusions Effectiveness of AT on anxiety has hardly been studied, so no strong conclusions can be drawn. This emphasizes the need for high quality trials studying the effectiveness of AT on anxiety.